2019
DOI: 10.1097/01.ogx.0000577812.20743.bf
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Year of Birth and 1-Year Survival Among Extremely Preterm Infants in Sweden During 2004–2007 and 2014–2016

Abstract: (Abstracted from JAMA 2019;321(12):1188–1199) The long-term health outcomes for preterm infants have improved over time, but infants born at extreme preterm gestational ages continue to present issues of optimal antenatal and postnatal management, resource allocation and costs, quality of care, and long-term health outcomes. To better understand variations and time trends for management and outcomes of extremely preterm birth, study of international populations is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 0 publications
3
79
2
1
Order By: Relevance
“…Our reported increased incidence may represent a real increase but also may be due to previously undetected cases. Increased survival of extremely preterm born could have added cases during the end of the study period . A contributing factor to a real increase might have been immigration, but according to our findings, this was less important.…”
Section: Discussionmentioning
confidence: 60%
“…Our reported increased incidence may represent a real increase but also may be due to previously undetected cases. Increased survival of extremely preterm born could have added cases during the end of the study period . A contributing factor to a real increase might have been immigration, but according to our findings, this was less important.…”
Section: Discussionmentioning
confidence: 60%
“…It is the main contributor to neonatal mortality and morbidity, moreover, this morbidity contributes to 40% of all deaths of children under 5 years of age . A Swedish national population‐based cohort study 2014‐2016 showed an unprecedented high survival (77%) of extremely preterm infants born between 22 and 26 weeks of gestation . One contributing factor to severe morbidity is the chronic lung disease, BPD, which is also a predictor of adverse long‐term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In neonatal care, we can increasingly save infants born at 22 weeks of gestational age and onwards and achieve a lower neonatal morbidity . This presents us with the challenge of not only ensuring the infant's viability but also providing care that promotes positive parental physical and mental health and that facilitates the development of a secure parent‐infant relationship.…”
Section: Introductionmentioning
confidence: 99%